2018
DOI: 10.17220/ijpes.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of CBT Group Counseling with Passive vs Active Music Therapy to Reduce Millennials Academic Anxiety

Abstract: The purpose of this research is to know the effectiveness of counseling group implementation of cognitive behavior therapy (CBT) approach with passive and active music therapy technique in reducing academic anxiety millennials students. This study used quasi-experimental design with repeated measures (pretest, posttest, and follow-up). Group counseling was conducted for 5 meetings (@ 100 minutes), and follow-up was performed after 2 weeks of treatment. Research subjects used in this study are 14 millennials ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
(35 reference statements)
0
15
0
1
Order By: Relevance
“…In addition, the researchers provide suggestions for students who still have anxiety in making decisions about their future careers, namely by providing motivation and counseling through music therapy. As research has been conducted in Indonesia, it is proven that music therapy can reduce anxiety ( Situmorang, 2018 , 2020a , 2020b ; Situmorang et al., 2018 ). This research can serve as a basis for new ideas to further investigate the relationship between these variables.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the researchers provide suggestions for students who still have anxiety in making decisions about their future careers, namely by providing motivation and counseling through music therapy. As research has been conducted in Indonesia, it is proven that music therapy can reduce anxiety ( Situmorang, 2018 , 2020a , 2020b ; Situmorang et al., 2018 ). This research can serve as a basis for new ideas to further investigate the relationship between these variables.…”
Section: Discussionmentioning
confidence: 99%
“…As an illustration of this, the young people in Bambling et al.’s (2008) and King et al.’s (2006) research accepted that their pastoral/spiritual counselors or psychologists regularly confused the enthusiastic substance of their messages. In addition, Situmorang (2018) , Situmorang, Mulawarman, and Wibowo (2018a , 2018b ), and Situmorang, Wibowo, and Mulawarman (2018) found that if the counseling process uses music therapy, especially if the counselor and counselee/client play music together online, there will be a sound delay.…”
Section: The Disadvantages Of Online/cyber Counselingmentioning
confidence: 99%
“… Step 4: Art-psychotherapy techniques Use psychotherapy techniques with art, such as music or drawing to get to know yourself and be able to get to know more about the client's needs ( McCluskey and O’Toole, 2019 ; Schaverien, 2000 ). Step 5: Accompani mentmusic During the tele-psychotherapy process, use a relaxing music accompaniment so that the psychotherapy process can run as comfortably and objectively as possible ( Situmorang, 2018 , 2020 ; Situmorang et al, 2018 ). …”
Section: Countertransference In Tele-psychotherapymentioning
confidence: 99%